Growth Increase of Gelam (Melaleuca Leucadendron) Burnt Peatland Through the Provision of Soil Conditioner (Study in Londerang Peat Protection Forest) - Rike Puspitasari Tamin; Richard Robintang Parulian Napitupulu; Jenny Rumondang; Rizky Ayu Hardiyanti (Postgraduate, University of Mataram, 2024)
The protected forest of Londerang Jambi is an area of hydrological unity with a surface area of 12.484 ha that is located in the district of Tanjung Timur and Muaro Jambi, which is surrounded by palm plantations and forest of industrial crops and 10 villages in the Districts of Tanjung Jabung Timur and Jambi. Based on the results of the Landsat 8 OLI image analysis and the SPOT 7 image interpretation by WWF Indonesia in 2015 that the Londerang Forest Protection Area (HLG) has an area of 12.848 Ha, currently the steep vegetation cover that canopies closely on the HLG Londerang remains only less than 10% of the area of HLG londerang due to forest fires in 2015. An attempt to overcome the situation has been made, one of them in the HLG Londerang being made an of the Hydrological Union of Mendahara-Sungai Batanghari which has been intervened by the Badan Restorasi Gambut (BRG). This effort was also carried out by the KIFC (Korea Indonesia Forest Center) by revegetating the blocks of land that had been burned in HLG Londerang. The planting has been carried out from the beginning of 2022 to December 2022. The species of plants planted among them are Pulai Rawa (Alstonia scholaris), Balangeran (Shorea balangeran), Gelam (Melaleuca leucadendron). In order to support the success of the revegetation, intensive maintenance is required, including the provision of soil fertilizers such as dolomite and NPK fertilizer. The research was conducted for seven months from May to December 2023 at HLG Londerang. Measuring fields are made with group random designs (RAK). The clustering is based on the difference in the height of the groundwater surface